CULTURE FUSION: EDUCATION HABBITS ON SOCIETY FOR INCLUSIF STUDENTS - Siti Mayang Sari; Mhd. Syafii; Akmaluddin Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Inclusive Education in Educational Equality and Habituation in Collaborative Culture Inclusive education is an approach that aims to provide equal access to education to all children, regardless of their background, abilities, or special needs. In the context of educational equality, inclusive education plays an important role in bridging social, economic, and cultural gaps. Collaborative culture is one of the main foundations to support the implementation of inclusive education, creating an inclusive and harmonious learning environment. Inclusive education implemented through a culture of collaboration is the key to equalizing education in society. By adopting a collaborative approach, all parties of the school, students, parents, and community contribute to creating a fair, friendly, and supportive learning environment. This not only provides equal opportunities to all students, but also builds a more inclusive, empathetic, and supportive society. A culture of collaboration is an essential element of inclusive education. It creates a learning environment that supports all students, promotes cooperation, and reduces social disparities.